MED15, encoding a subunit of the mediator complex, is overexpressed at high frequency in castration‐resistant prostate cancer. Issue 1 (9th December 2013) - Adler, David; Menon, Roopika; Braun, Martin; Offermann, Anne; Queisser, Angela; Boehm, Diana; Vogel, Wenzel; Rüenauver, Kerstin; Ruiz, Christian; Zellweger, Tobias; Svensson, Maria; Andren, Ove; et al.
Abstract : The mediator complex is an evolutionary conserved key regulator of transcription of protein‐coding genes and an integrative hub for diverse signaling pathways. In this study, we investigated whether the mediator subunit MED15 is implicated in castration‐resistant prostate cancer (CRPC). MED15 expression and copy number/rearrangement status were assessed by immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH), respectively on 718 prostate cancer (PCa) specimens and sequenced by Sanger on a subset. Furthermore, SMAD3 phosphorylation, androgen receptor (AR) and proliferation markers were evaluated by IHC. In PCa cells, siRNA/shRNA knockdown of MED15 was followed by proliferation assays with/without dihydrotestosterone (DHT), and treatments with recombinant TGF‐β3. Our results show that MED15 is overexpressed in 76% of distant metastatic CRPC (CRPC MET ) and 70% of local‐recurrent CRPC (CRPC LOC ), in contrast to low frequencies in androgen‐sensitive PCa, and no expression in benign prostatic tissue. Furthermore, MED15 overexpression correlates with worse clinical outcome thus defining a highly lethal phenotype. Moreover, TGF‐β signaling activation associates with MED15 overexpression in PCa tissues, and leads to increased expression of MED15 in PCa cells. MED15 knockdown effects phosphorylation and shuttling of p‐SMAD3 to the nucleus as well as TGF‐β‐enhanced proliferation. In PCa tissues, MED15 overexpression associates with AR overexpression/amplification and correlates with high proliferative activity. MED15 knockdown decreases both androgen‐dependent and ‐independent proliferation in PCa cells. Taken together, these findings implicate MED15 in CRPC, and as MED15 is evolutionary conserved, it is likely to emerge as a lethal phenotype in other therapeutic‐resistant diseases, and not restricted to our disease model. Abstract : What's new? MED15, a subunit of the Mediator transcriptional regulator complex, has been implicated in castration‐resistant prostate cancer (CRPC). This study shows that 70 percent of local‐recurrent CRPCs and 76 percent of distant metastatic CRPCs overexpress MED15 and that MED15 overexpression defines a highly lethal phenotype. MED15 expression was found to be increased by TGF‐ß activation, such that MED15 knockdown affected TGF‐β signaling and TGF‐β‐enhanced proliferation. Knockdown also resulted in decreased androgen‐dependent and ‐independent proliferative activity. The findings, taken together with the evolutionary conservation of MED15, suggest that MED15 in CRPC may be a model of therapeutic‐resistant disease.